1988
DOI: 10.1093/carcin/9.7.1323
|View full text |Cite
|
Sign up to set email alerts
|

Serum albumin adducts in the molecular epidemiology of aflatoxin carcinogenesis: correlation with aflatoxin B1 intake and urinary excretion of aflatoxin M1

Abstract: Aflatoxin-serum albumin adducts in the blood of 42 residents of Guangxi Province, People's Republic of China, were determined and compared with intake of aflatoxin B1 (AFB1) and excretion of aflatoxin M1 (AFM1) in urine. Blood specimens were obtained during the same period that urine was collected and that diet was sampled. Serum albumin was isolated from blood by affinity chromatography on Reactive Blue 2-Sepharose and subjected to enzymatic proteolysis using Pronase. Immunoreactive products were purified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0
10

Year Published

1991
1991
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(122 citation statements)
references
References 0 publications
5
107
0
10
Order By: Relevance
“…AF contamination in food has been a long-term problem in Uganda (Alpert et al 1971;Kaaya & Warren 2005;Kitya et al 2010). While contamination by the AF-producing Aspergillus fungi may be universal within a given geographical area, the levels or final concentration of AF in the grain product can vary from < 1 µg kg -1 (1 ppb) to > 12 000 µg kg -1 (12 ppm) (Gan et al 1988). For this reason, the measurement of human consumption of AF by sampling foodstuffs is imprecise.…”
Section: Discussionmentioning
confidence: 99%
“…AF contamination in food has been a long-term problem in Uganda (Alpert et al 1971;Kaaya & Warren 2005;Kitya et al 2010). While contamination by the AF-producing Aspergillus fungi may be universal within a given geographical area, the levels or final concentration of AF in the grain product can vary from < 1 µg kg -1 (1 ppb) to > 12 000 µg kg -1 (12 ppm) (Gan et al 1988). For this reason, the measurement of human consumption of AF by sampling foodstuffs is imprecise.…”
Section: Discussionmentioning
confidence: 99%
“…13 AFM 1 is one of the major metabolites found in the urine of subjects exposed to AFB 1 in vivo, and its level correlates with the presence of AFB 1 -serum albumin adducts, an established biomarker for dietary exposure to aflatoxins. 2,[14][15][16] However, quantitative data on AFM 1 excretion into feces are limited. On the other hand, CYP3A4 is known as one of the major CYP enzymes in the liver, 13,[17][18][19][20] and in vitro studies using primate and human liver microsomes have demonstrated that AFQ 1 is a major AFB 1 metabolite.…”
Section: Guanine; Hepatitis B Virusmentioning
confidence: 99%
“…Based upon knowledge of AFB 1 metabolism, a number of molecular dosimetry markers of aflatoxin exposure have been developed (Gan et al, 1988;Groopman et al, 1992;Yu et al, 1997). Among them the AFB 1 -albumin adduct has been a useful biomarker reflecting long-term exposure to aflatoxins in different populations (Gan et al, 1988;Wild et al, 1990) and linking to an elevated risk of HCC (Chen et al, 1996a,b;Wang et al, 1996b;Sun et al, 2001). Thus, exploring the determinants of formation of AFB 1 -albumin adducts may contribute to understanding the complex interaction among multiple risk factors involved in hepatocarcinogenesis.…”
Section: Epidemiologymentioning
confidence: 99%
“…Many studies have confirmed that parent compound AFB 1 is converted to its carcinogenic forms through metabolism by members of the endogenous cytochrome P-450 enzyme superfamily to reactive 8,9-epoxide metabolites, which can covalently interact with cellular DNA and proteins (International Agency for Research on Cancer, 1992;Gallagher et al, 1994;Guengerich et al, 1998). Among the major epoxide-derived macromolecular adducts identified, the AFB 1 -albumin adduct correlates well with other aflatoxin measurements and provides a cumulative measure of exposure over several months in humans (Wild et al, 1986;Gan et al, 1988).…”
mentioning
confidence: 99%